1997
DOI: 10.1021/la970231s
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interfacial Tension in Nucleation beneath Monolayer Films

Abstract: Monolayer films at high surface pressures are well-ordered, and due to their 2D crystallinity they can act as sites of preferential nucleation. Recently it has been demonstrated that films at lower surface pressures can also be preferential nucleators, despite their decreased ordering. In this study we show that identifying the factors which can reduce the interfacial tension is vital to understanding the varied mechanisms through which nucleation beneath monolayer films can occur. In particular, the preferent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Cooper et al, [27,28] indicated that in order to promote nucleation, it is not necessary to have a highly organized monolayer. Monolayers at low or medium pressure, in which a greater dynamical freedom and compressibility occurs, can lead to higher nucleation rates.…”
Section: Effect Of Surface Pressure On the Nucleation Of Com Under Dpmentioning
confidence: 99%
“…Cooper et al, [27,28] indicated that in order to promote nucleation, it is not necessary to have a highly organized monolayer. Monolayers at low or medium pressure, in which a greater dynamical freedom and compressibility occurs, can lead to higher nucleation rates.…”
Section: Effect Of Surface Pressure On the Nucleation Of Com Under Dpmentioning
confidence: 99%
“…Second, the monolayers at low pressures have a greater dynamic freedom and compressibility. 3,39, 40 The monolayer interfaces at low pressure have the ability to optimize the…”
Section: Sa Monolayers At Low Surface Pressure Catalyze the Heterogen...mentioning
confidence: 99%
“…31 Cooper, Sessions, and Lubetkin studied amino acid nucleation under partially compressed films and concluded that the ability of the film to reorganize to reduce interfacial energy can optimize nucleation. 32,33 In subsequent publications a mixture of mechanisms began to be represented, with some still emphasizing structure-based molecular recognition [34][35][36][37][38] and others discussing interfacial electrostatics as the predominant mechanism. [39][40][41][42][43][44][45][46][47][48][49] Experiments which highlighted the importance of monolayer adaptability included calcium oxalate grown under phospholipid films; [50][51][52] hydroxyapatite under fatty acids; 53 observations by Brewster Angle Microscopy of mineralization at domain boundaries of Langmuir films, where it can be argued that molecules shift to accommodate crystal nuclei; 54,55 and computational studies.…”
Section: Mineralization At Monolayer Filmsmentioning
confidence: 99%